A construção de representações sociais sobre o educando na relação professor - aluno - Vieira, André Vitorino (2001)
The present study consists of a research work carried out in a state school in the city of Uberlândia. The work aims to identify and analyze the social representations about the student in the teacher-student relationship; as well as its influences on the learning process of the students with school failure. To this end, six teachers from that state school interviewed me, five students attending the Basic Literacy Cycle and presenting academic failure according to the teachers. Also interviewed was one responsible for each student. I used two semi-structured interview models as a data collection instrument, one specific for the teacher and one for students and their families. The content of the interviews was analyzed based on the proposed objective, the problematization of the theme and in the light of the Theory of Social Representations as well as authors who work with the daily school life and theoretically subsidized this research. In the considerations I suggest that the social representations of teachers is another intra-school factor that contributes to the existence of school failure, and the students, when apprehending them, begin to express and behave according to the perceptions existing in their teachers' representations.